Genetic trade‐offs between complex diseases and longevity. Issue 7 (26th June 2022) - Hu, Dingxue; Li, Yan; Zhang, Detao; Ding, Jiahong; Song, Zijun; Min, Junxia; Zeng, Yi; Nie, Chao
Abstract: Longevity was influenced by many complex diseases and traits. However, the relationships between human longevity and genetic risks of complex diseases were not broadly studied. Here, we constructed polygenic risk scores (PRSs) for 225 complex diseases/traits and evaluated their relationships with human longevity in a cohort with 2178 centenarians and 2299 middle‐aged individuals. Lower genetic risks of stroke and hypotension were observed in centenarians, while higher genetic risks of schizophrenia (SCZ) and type 2 diabetes (T2D) were detected in long‐lived individuals. We further stratified PRSs into cell‐type groups and significance‐level groups. The results showed that the immune component of SCZ genetic risk was positively linked to longevity, and the renal component of T2D genetic risk was the most deleterious. Additionally, SNPs with very small p ‐values ( p  ≤ 1x10 ‐5 ) for SCZ and T2D were negatively correlated with longevity. While for the less significant SNPs (1x10 ‐5  <  p  ≤ 0.05), their effects on disease and longevity were positively correlated. Overall, we identified genetically informed positive and negative factors for human longevity, gained more insights on the accumulation of disease risk alleles during evolution, and provided evidence for the theory of genetic trade‐offs between complex diseases and longevity. Abstract : Lower genetic risks of stroke and hypotension were observed in centenarians, while higher genetic risks of schizophrenia (SCZ) and type 2 diabetes (T2D) were detected in long‐lived individuals. The immune component of SCZ genetic risk was positively linked to longevity, and the renal component of T2D genetic risk was the most deleterious. For variants that most significant in SCZ decreases lifespan whereas those less significant variants increases lifespan.